Intelligence science and big data engineering : 5th international conference, ISCIDE 2015, Suzhou, China, June 14-16, 2015 : revised selected papers /: 5th international conference, ISCIDE 2015, Suzhou, China, June 14-16, 2015 : revised selected papers. (2015) - Unknown
No abstract available